Comparison of the porosity characteristics of Portland cement, mineral trioxide aggregate and Biodentine by scanning electron microscopy - Bravo Eslava, Luis Manuel (2021)
Objective: The purpose of this study was to compare the porosity characteristics of Portland cement, mineral trioxide aggregate (MTA) Angelus® and Biodentine Septodont® by scanning electron microscopy. Materials and Methods: Cements were prepared according to the manufacturer's instructions and packed in cylindrical polyethylene tubes with an internal diameter of 10 mm and a height of 5 mm. The porosity of the samples was analyzed using scanning electron microscopy. Statistical analyses were performed using the Kruskall Wallis test. The level of significance was established at 0.05. Results: The largest size mean diameter valus was found with Portland cement (11.07). There were significant differences between the mean pore diameters (p = 0.05). MTA Angelus® had the largest number of pores, followed by Biodentine Septodont®, and finally, Portland. There were no significant differences in the pores of the three cements (p =0.09). Conclusion: The results of this comparative analysis of endodontic cements showed that Portland cement has a larger pore diameter than MTA Angelus® and Biodentine Septodont®, demonstrating that these latter two cements present better resistance and permeability properties, and thereby prevent microleakage.